Re-examining the 1948 Revolt of the Malayan Communist Party in Malaya - C.C. Chin (Kajian Malaysia, 2009)
This paper brings forward the idea of MCP’s plan for the revolt by examining various MCP documents at that time and oral history records of several important senior MCP cadres in order to determine its rationale. The MCP original document, especially those resolutions passed during the Central Committee Meetings suggest that the MCP did have a plan for revolt. An analytical approach of the MCP documents will help to determine whether the action taken by the MCP was simply an inevitable action against British repression rather than an act that took place because of external forces. Within the MCP, there were also arguments and debates regarding the revolt. Was the revolt necessary and were constitutional means completely exhausted? Could lack of alertness and adventurism be blamed for the ill-prepared revolt? The paper also examines if the Cold War setting in Asia was intentional on the part of the British. By examining British and Australian archival sources and CIA reports, we can determine to what extent the British in collaboration with the Australians and Americans, acted intentionally to extend the Cold War to Asia and create a confrontational situation in order to contain Southeast Asian Communism. In short, were the imperialists responsible for the armed revolts in Southeast Asia?